Revisiting Parquet Deformations from a computational perspective: A novel method for design and analysis. (December 2017) - Yazar, Tuğrul
Parquet Deformation is an architectural studio exercise introduced by William Huff in 1960s. It aims to improve students' reasoning of spatiotemporal variation by utilizing sequential shapeshifting of patterns. This article examines the outcomes of this educational research from a perspective of design computing with a purpose to remark its pedagogical significance. A multilayered reading about the exercise will reveal its historical, theoretical, and artistic backgrounds. Then the common structural elements and different construction approaches are explained along with a novel design and analysis method. The proposed method embeds variations of two-dimensional pattern deformations on a third dimension. It enables various analyses such as the measurement of regularity and locating the attractor points. This study is expected to exemplify how computational thinking and new digital tools change the way designers would approach to such systematic compositions.